James Barr and Biblical Inspiration: A Critique of Barr's view of Biblical inspiration in the light of recent exegetical and theological developments in Evangelical Theology - Wethmar, Conrad Johannes (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2004.